Relationship Between Economy and Moderation of Religion in Mororejo Village, Tosari District, Pasuruan Regency - Lathifah, Nurul; Utami, Betty Silfia Ayu; Debby Nindya, Istiandari; Yusman, Beta Aria Nur Azizah; Pratiwi, Nur Fadillah Wahyuni Eka (OECONOMICUS Journal of Economics, 2025)
Economy and moderation are two things that cannot be separated. The relationship between the economy and moderation can be seen in Mororejo Village, Tosari District, Pasuruan Regency, empowering economic potential through increasing levels of productivity has a relationship to conditions of religious moderation in society, where people can accept religious differences that occur in their environment without discriminatory attitudes towards adherents minority religion. The attitude of acceptance of religious differences that occur also indirectly shows how the relationship of religious moderation is to economic conditions in Mororejo Village, where mutual tolerance and willingness to work together between religious adherents contribute to increasing the average production of the agricultural sector and raise people's average income.